2020
DOI: 10.5194/egusphere-egu2020-9785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Full characterization of the ML 5.4 2019/11/11 Le Teil earthquake in France based on a multi-technology approach

Abstract: <p>Metropolitan France is a region of slow tectonic deformation rates with sparse historical and instrumental seismicity, and where geodesy is not able to reach the required resolution in order to resolve the tectonic loadings. The few faults recognized as potential active rely on rare neotectonic slip rates, often integrated over geological scales.</p><p>In this context, the M<sub>L</sub> 5.4 Le Teil 2019 earthquake is of parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The inverted depth lies around 1 km and the calculated moment magnitude is Mw 4.8 (Vallage et al, 2020), which is in agreement with other publications (Ritz et al, 2020;Cornou et al, 2021) and with rapid estimations from different French institutes such as OCA (Mw 4.9, 1 km) and IPGP (Mw 4.8, 3 km). The moment magnitude estimated from coda wave analysis at 14 LDG stations is slightly higher (Mw coda 5.2), in between the ML and the other moment magnitudes (Tab.…”
Section: Le Teil (2019)supporting
confidence: 92%
See 1 more Smart Citation
“…The inverted depth lies around 1 km and the calculated moment magnitude is Mw 4.8 (Vallage et al, 2020), which is in agreement with other publications (Ritz et al, 2020;Cornou et al, 2021) and with rapid estimations from different French institutes such as OCA (Mw 4.9, 1 km) and IPGP (Mw 4.8, 3 km). The moment magnitude estimated from coda wave analysis at 14 LDG stations is slightly higher (Mw coda 5.2), in between the ML and the other moment magnitudes (Tab.…”
Section: Le Teil (2019)supporting
confidence: 92%
“…Ultimately, InSAR measurements made with Sentinel 1 imagery clearly highlight surface deformation located on the Rouvière fault. The InSAR inversion revealed that the maximum amount of slip was localized at about 1 km depth and displacements were observed up to the surface (Vallage et al, 2020;Ritz et al, 2020).…”
Section: Le Teil (2019)mentioning
confidence: 99%